KRITIK TERHADAP PEMASARAN BANK SYARIAH (PENDEKATAN EKSPERIENTAL MARKETING) - Rinda Asytuti (Jurnal Hukum Islam, 2012)
This study examines the idea of Bernard Schmitt, ‘experiential marketing’, on Islamic banks that are operating side by side with conventional banks. This marketing is a concept that integrates elements of emotions, logic, and general thought processes to connect with the consumer. The goal of experiential marketing is to establish the connection in such a way that the consumer responds to a product offering based on both emotional and rational response levels. Via "experiential marketing," Schmitt presents a revolutionary framework for getting in-touch with one's customers while at the same time differentiating oneself from rest of the competition. Here are a few of the basics of experiential marketing for Islamic banks, and how this process can often succeed when other marketing strategies fail.